WAYS TO IMPROVE THE QUALITY OF BAKERY PRODUCTS BASED ON MODERN BIOTECHNOLOGY (Web of Technology: Multidimensional Research Journal, 2025)
Bread is considered one of the oldest and most consumed foods in the history of mankind. And its quality is important not only to ensure the health and satisfaction of consumers, but also to the development of the food industry. In recent years, advances in biotechnology have been creating new opportunities to increase quality in bread production. This article provides information on ways to improve the quality of bakery products with the help of modern biotechnology.